Preparation and characterization of vanado-, ferri-, and gallosilicate catalysts in the presence of fluoride ions - Hong, S.B.; Kim, C.G.; Uh, Y.S.; Park, Y.K.; Woo, S.I. (Springer-Verlag, 1992)
Vanado-, ferri-, and gallosilicate catalysts were prepared from the mixtures containing colloidal silica, corresponding metal source, tetrapropylammonium bromide, and NH4F by hydrothermal crystallization at 175°C for 7 days. The pH value of the reaction mixture was low (pH<8) compared to the conventional methods. The metal compounds have higher solubilites in these conditions than conventional conditions (pH>10). The size distribution and the size of final products were found to be more homogeneous and larger than those of metallosilicates prepared in strong alkaline media. The characterization of metallosilicates with IF!, X-ray diffraction, SEM, EPR, and29Si MAS NMR, indicated that corresponding metal atoms were successfully incorporated into the tetrahedral lattice sites of the ZSM-5 structure. ？ 1992 Korean Institute of Chemical Engineering.